2019
DOI: 10.1016/j.fsigen.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 21 autosomal STRs in Saudi Arabia reveals population structure and the influence of consanguinity

Abstract: Variation in the 21 autosomal STRs detected by the GlobalFiler multiplex was investigated in a sample of 523 indigenous male Arabs from five geographic regions of Saudi Arabia. Although allele frequencies for the entire dataset were found to be broadly similar to those determined in previous studies of Saudi citizens, significant differences were found among regions. Heterozygote deficiency was observed at nearly all loci in all regions, probably as a consequence of high levels of consanguineous marriage; in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
8
13
2
Order By: Relevance
“…Other applications include population genetics, anthropology, and epidemiology studies investigating the risk of prostate cancer (Paracchini et al 2003;Hameed et al 2015). Because of its crucial geographical location in the Arabian Peninsula and in the Gulf of Oman, several authors have studied Y chromosome diversity in native Saudi population employing Y-STR technology (Cadenas et al 2008;Abu-Amero et al 2009;Alshamali et al 2009;Khurbani et al 2018Khurbani et al , 2019. The current report presents the population data for 17 Y-STR loci among 125 adult, native, Saudi male volunteers recruited from different geographic regions of Saudi Arabia (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Other applications include population genetics, anthropology, and epidemiology studies investigating the risk of prostate cancer (Paracchini et al 2003;Hameed et al 2015). Because of its crucial geographical location in the Arabian Peninsula and in the Gulf of Oman, several authors have studied Y chromosome diversity in native Saudi population employing Y-STR technology (Cadenas et al 2008;Abu-Amero et al 2009;Alshamali et al 2009;Khurbani et al 2018Khurbani et al , 2019. The current report presents the population data for 17 Y-STR loci among 125 adult, native, Saudi male volunteers recruited from different geographic regions of Saudi Arabia (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Other studies have shown that sample selection bias can affect population structure analysis of genotype data, genetic ancestry of individuals, and evolutionary history of a certain population (Rosenberg et al 2002;Patterson et al 2006). Most of the studies carried out in the Saudi population (Cadenas et al 2008;Abu-Amero et al 2009;Alshamali et al 2009;Khurbani et al 2018Khurbani et al , 2019 are based upon the sample collected either from Saudi blood banks, hospitals, forensic casework samples, or from native Saudis living abroad who are mostly self-declared and are not subjected to any type of further verification therefore, lacking the reliable ethnic or demographic originality that may affect, to some extent, the outcome of population genetic parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Lebanon (LEB) and an Indian (IND) population from Madhya Pradesh typed for the 23 autosomal loci 24 were also included in the analysis. Genetic distance was also assessed at a regional level using allele frequencies for the 13 of the 23 autosomal loci (CSF1PO, D13S317, D16S539, D18S51, D21S11, D3S1358, D5S818, D7S820, D8S1179, FGA, TH01, TPOX, vWA) that are shared between the data reported in this study and other studies of Kuwait and neighbouring counties: Kuwait (KW1 3 and KW2 2 ), Iran (IRN 25 and IRN1 2 ), Saudi Arabia (SA 26 and SA1 27 ), Qatar (QAT 28 ), Oman (OMN 29 ), Yemen (YEM 29 ), United Arab Emirates (UAE 30 ), Bahrain (BAH 31 ), and Iraq (IRQ 32 and IRQ1 2 ). PCA analysis was conducted using R software 33 and visualised using the factoextra package 34 .…”
mentioning
confidence: 77%
“…Saudi Arabia is the largest country in the Arabian Peninsula with a population exceeding 32 million where people are non-uniformly distributed [12]. Nearly half of the population resides in two major administrative provinces, Riyadh and Mecca [13].…”
Section: Introductionmentioning
confidence: 99%